Isolation and identification of a new Bacillus strain for amylase production - Bakri, Yasser; Ammouneh, Hassan; El-Khouri, Samir; Harba, Muhanad; Thonart, Philippe (Research in Biotechnology, 2012)
The objective of the study was to isolate amylase producing bacteria from Syrian soil samples. Amylolytic Bacillus sp were isolated on starch agar medium. The Bacillus SY134D was the best amylase producing isolate among two hundred and ten isolates showed the amylolytic activity. The closest phylogenetic neighbours according to 16S gene sequence, the Bacillus SY134D isolate was identified as Bacillus subtilis. The optimum temperature for amylase production was found to be 37Ã‚Â°C. AmylaseÃ‚Â production occurred at pH 3.0-9.0 with a maximum at pH 5.0. The best enzyme activity was observed at pH 6.0 and temperature 70Ã‚Â°C.